Pengaruh Upah Minimum Dan Pengangguran Terhadap Kemiskinan di Pulau Jawa Sebelum dan Selama Pandemi Covid-19 - Muhammad Farhan Dakhilullah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Poverty is a fundamental issue, since poverty involves meeting the most vital needs of life and is a problem that many countries face, including Indonesia. Since its entry into and development of the covid-19 pandemic into Indonesia in the early part of 2020, putting immense pressure on the economic sector and affecting the social life of communities. In general, the condition of the number of poor people in each province on Java both before and after the entry of covid-19 was not marked by a change in ratings, which indicates an increase in average value. The study was intended to see how the minimum wages of the province and unemployment rates of the 6 provinces on Java period 2017 to 2021 and to see how the covid-19 diagnosis of covid-19 against poverty, the regression of the data panel analysis was made with the random effect model diman's approach that the minimum labor would not affect poverty, Unemployment has a negative impact on poverty and the covid-19 pandemic has a positive impact on the growing number of poor people on the island of Java.